(untitled) (Research, Society and Development, 2022)
Genetics has been the subject of great scientific and technological advances. However, the textbooks used High School hinder understanding, and does not instigate the critical and reflexive view of the students. The compatibility of the ABO system, determined by the blood groups inherited by the individuals, is an important topic in teaching, because in blood transfusion we need to avoid incompatibility that brings drastic consequences to the health. The aim was creating original low-cost didactic materials to teach about the ABO system and evaluate the student interest on topic, and the teacher’s opinion about the use of the didactic material. For this, teaching materials were prepared in the extension project “Popularizing Genetics” and evaluated in two consecutive years. In the first year, a visual assessment of students’ interest and attention was performed during the presentation of the ABO blood system topic using a “test” didactic model. In the second year, the model was improved, and two other high schools were tested using the case study model with assessments carried out through questionnaires for teachers and students. Statistical tests indicated positive results to improve interest and understanding of the ABO system. However, the teachers’ opinion was controversial.